THE ROLE OF VARK TECHNOLOGY IN DEVELOPING CREATIVE COMMUNICATIVE (Yangi O'zbekistonda Tabiiy va Ijtimoiy-gumanitar fanlar respublika ilmiy amaliy konferensiyasi, 2026)
This study examines the pedagogical potential of the VARK model in enhancing creative communicative competence among language learners. It integrates theoretical perspectives from leading scholars and highlights the role of multimodal learning in fostering adaptability, creativity, and effective communication skills.